2006
DOI: 10.1016/j.intcom.2005.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Usability professionals—current practices and future development

Abstract: The usability concept has now received such a wide recognition in information technology (IT) development that working with usability can be regarded as a profession in its own right. In recent research projects, we have surveyed and studied usability work on an individual level in a number of Swedish development organisations, including success factors and obstacles. What we have seen relates to the individual usability professional and her background and experiences, the organisation in which she operates, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 40 publications
2
96
0
2
Order By: Relevance
“…Gulliksen and his research group have reported numerous studies, mostly concerning public authorities in Sweden [e.g. 3,12,13], while Iivari has analyzed usability specialists work practices in product development in Finland [15,16]. These are qualitative inquiries on the matter, but there is also some survey research carried out [6,12,37] 26,27], reporting on usability specialists' ways of working when face-to-face contact is impossible.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…Gulliksen and his research group have reported numerous studies, mostly concerning public authorities in Sweden [e.g. 3,12,13], while Iivari has analyzed usability specialists work practices in product development in Finland [15,16]. These are qualitative inquiries on the matter, but there is also some survey research carried out [6,12,37] 26,27], reporting on usability specialists' ways of working when face-to-face contact is impossible.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…On one hand, the HCI literature has touched upon the issue in the sense that it maintains that usability specialists have to act as usability champions and evangelists inside their organizations and try to seduce and convince numerous stakeholder groups, i.e. developers, managers, sales, marketing and documentation, to buy into usability [2,8,13,15,16,25,37]. On the other hand, the literature on multiparty IT development efforts reveals that there nowadays are parties from numerous organizations and even countries involved, representing different kinds of areas of expertise: not only technology, marketing and business, but also strategy, manufacturing, education, curation, meteorology etc.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations